Gasevaporated moisture as the geologic-geochtmical phenomenon of the planetary scale - Vasiliy Ivanovich Petrenko; Nickolay Nickolaevich Petrenko; Ivan Nickolaevich Petrenko (Наука. Инновации. Технологии)
The process of forming the gasevaporated moisture is already being itself the unique geochemical phenomenon. This has visually been proved by the presence of aqueous vapour in the gas and gas-condensate deposits of the zones of the earth core in which owing to high fluid pressure the water can be present only in a liquid phase within the undercritical temperatures for fresh water (373 °C) and its brines (400-600 °C). The appearance in this zone, as a rule, always watersaturated, of the free gas accumulation, from nucleus bubbles to the whole deposits, leads to the formation of the double system as vapourgas mixtures. In the mentioned mixtures the aqueous vapor is always present of gasevaporated moisture (aqueous vapour formed as a result of the gas free accumulation which evaporated the liquid water). This had been proved by the nomerous experiments in the high pressure installations and by the development of numerous domestic and foreign gas and gas-condensate deposits and also the caps of oilgas deposits. The moisture content of the vapourgas mixtures depends on the gas ,moistures (CH4, CO2, H2S, N2 and so on), thermobaric parameters of the system (that is, pressure and temperature in the hydrocarbon deposits), mineralization of the water conjugated with gas) the residual water in the deposit. Gasevaporated moisture and its derivate as the condensational water takes part in the manifestation of a great number of geologic and geochemical processes both in the hydrocarbon deposits and in the earth core. The important peculiarity of the e gasevaporated moisture is mass transfer of chemical elements including rare earths. The results of the given work have been the laborious investigations on the mentioned problem for many years.